Fulfillment of The Principle of The Best Interest of Children in The Granting of Child Marriage Dispensation in Indonesia - Gina Wulandari; Tirtawening Paritkesit (IHSA Institute, 2022)
The purpose of this paper is to analyze how the fulfillment of the principle of the best interests of the child in the consideration of the Panel of Judges to provide dispensation for child marriage. Indonesia occupies the 10th position with the highest child marriage rate in the world in 2020. The National Development Planning Agency states that 1,220,900 Indonesian children are married before an early age. The problem of child marriage is indeed one of the problems that has occurred for a long time, but until now it has not been able to be solved. One of the efforts made by the Government to suppress the high number of child marriages in Indonesia is by increasing the minimum age for marriage through Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage (Marriage Law). The provisions in Article 7 paragraph (1) of the Marriage Law change the minimum age for marriage which was previously 16 years for women and 19 years for men to 19 years for women and men. However, the provisions in Article 7 paragraph (2) open the opportunity for marriages under the specified age to be carried out, namely requesting a dispensation from the Court on the grounds that it is very urgent.